Substitution:

Change second equation to point slope:

y=-3x-13

9x-2y=27<---Second Eq.

2y = 9x - 27

y = (9x - 27)/2

y=-3x - 13

Since they both equal y, you can set them equal to each other.

(9x - 27)/2 = -3x - 13 -------------Multiply both sides by 2

9x - 27 = -6x - 26

15x = 1

x = 1/15

Now plug this into either of the equations to get y. I will do the first one

y = -3x - 13 ---------Plug in 1/15 for x

y = -3/15 -13

y = -1/5 - 13

y = -13 1/5

y = -66/5 OR -13.2

x = 1/15 OR 0.06666666666666666666666666666666666666666666666666666667

Elimination Method-->

Set first equation to standard form.

y = -3x - 13<--------First Equation

9x - 2y = 27

y = -3x - 13

y + 3x = -13<-------------Standard form

-2y + 9x = 27<------------Flipped x and y on the left side. Doesn't change the original equation

Now multiply the top equation by 2

2(y + 3x) = 2 * -13

2y + 6x = -26

-2y + 9x = 27

Now add both equations. This eliminates y so now you can solve for x.

2y + 6x -2y + 9x = -26 + 27

15x = 1

x = 1/15

Now you just do the stuff we did for substitution and solve for y.

y = -3x - 13 ---------Plug in 1/15 for x

y = -3/15 -13

y = -1/5 - 13

y = -13 1/5

y = -66/5 OR -13.2<-----------------------------------------------------------------------------------------Answer for y

x = 1/15 OR 0.06666666666666666666666666666666666666666666666666666667<-----Answer for x